Schumpeter Lecture 2021: Global Income Inequality, 1820–2020: the Persistence and Mutation of Extreme Inequality. Issue 6 (22nd October 2021) - Chancel, Lucas; Piketty, Thomas
Abstract: In this paper, we mobilize newly available historical series from the World Inequality Database to construct world income distribution estimates from 1820 to 2020. We find that the level of global income inequality has always been very large, reflecting the persistence of a highly hierarchical world economic system. Global inequality increased between 1820 and 1910, in the context of the rise of Western dominance and colonial empires, and then stabilized at a very high level between 1910 and 2020. Between 1820 and 1910, both between-countries and within-countries inequality were increasing. In contrast, these two components of global inequality have moved separately between 1910 and 2020: Within-countries inequality dropped in 1910–1980 (while between-countries inequality kept increasing) but rose in 1980–2020 (while between-countries inequality started to decline). As a consequence of these contradictory and compensating evolutions, early 21st century neo-colonial capitalism involves similar levels of inequality as early 20th century colonial capitalism, though it is based on a different set of rules and institutions. We also discuss how alternative rules such as fiscal revenue sharing could lead to a significant drop in global inequality. (JEL: N30, O10, O40)